Reactualizing Qur'anic Environmental Ethics for Sustainable Urban River Management - Rasyid, Muhammad Raihan Al; Muchtar, Muhammad (Universitas Muhammadiyah Surakarta, 2026)
This article aims to reactualize Qur'anic environmental ethics as a normative foundation for sustainable urban river management. The study highlights three major problems contributing to river degradation in urban areas: (1) fraudulent practices by the community in constructing houses, shop-houses, and permanent buildings on river buffer zones, which are legally classified as state land and are not subject to private ownership or trade; (2) low public ecological awareness, as reflected in irresponsible behaviors such as disposing of household waste and garbage into rivers; and (3) the lack of trustworthiness (amanah) on the part of the government in carrying out its duties, particularly in the weak supervision and control of illegal buildings along riverbanks. These practices have led to river narrowing, sedimentation, and obstructed water flow, thereby increasing the risk of flooding during periods of heavy rainfall. Through a thematic exegetical approach with an ecotheological perspective, this study affirms that the Qur'an contains fundamental principles such as amanah (trust), justice, the prohibition of fasād fī al-ard (corruption on earth), and collective responsibility in maintaining environmental balance. The reactualization of these values is expected to foster moral awareness within society and strengthen governmental integrity, enabling the realization of sustainable, just, and ethically grounded urban river management in accordance with Islamic teachings.